Polyurethane polystyrene foam as well as preparation method and application thereof
By combining components A and components B of specific formulas, polyurethane foam with high flame retardant properties and low density is formed, solving the dual challenges of foaming rubber density and flame retardant effect for power batteries, achieving excellent Combined with flame retardant properties and low density.
Patent Information
- Application Number
- CN202411220436.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2024-12-20
AI Technical Summary
While improving the flame retardant effect, the existing polyurethane foam glue increases its density, which cannot meet the low-density needs of foam glue for power batteries, and the flame retardant effect is poor under the limit of flame retardant content.
Using components A and B of specific formulas, including polyether polyols, isocyanates, composite flame retardants, silane coupling agents and catalysts, the polyurethane foam is compounded to improve flame retardant performance and dielectric strength. At the same time, the density and thermal conductivity are reduced.
A combination of high flame retardant effect and low density is achieved to meet the needs of foam glue for power batteries, flame retardant grade UL94-V0, dielectric strength > 3kV/mm, thermal conductivity <0.1W/(m·K), compression strength >3MPa.
Smart Images

Figure BDA0005022857110000021 
Figure BDA0005022857110000041 
Figure BDA0005022857110000051
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of power batteries, and in particular to a polyurethane foam and a preparation method and application thereof. Background Art
[0002] In recent years, the new energy vehicle industry has developed rapidly, and the share of new energy vehicles in the Chinese automobile market will continue to grow in the next few years. As various automobile manufacturers have achieved "high mileage" and "high energy density" for new energy vehicles through the optimization of materials and structures, safety issues have become particularly important. Power batteries are the core components of new energy vehicles, and improving power battery safety is the core element to improve the safety of new energy vehicles.
[0003] Battery foam plays an important role in new energy vehicle power batteries. It provides a strong guarantee for the safe, stable and efficient operation of batteries through its lightweight, excellent sealing performance, flame retardant performance, good weather resistance and stability. At present, under the background of stricter safety and environmental protection requirements, new challenges have been raised to the flame retardant effect of battery foam, requiring it to meet the flame retardant effect and not use halogen flame retardants. In addition, in order to reduce the density of the foam after curing, the amount of foam flame retardant used is also limited, resulting in poor overall flame retardant effect of battery foam.
[0004] Patent CN115368527A discloses a polyurethane foam material for cylindrical battery modules, a preparation method and application thereof, wherein the polyurethane foam material comprises component A and component B, wherein component A comprises polymer polyol A, a foaming agent, a halogen-free flame retardant and a catalyst; and component B comprises polymer polyol B, an isocyanate and a tackifier. Although the polyurethane foam material disclosed in the patent has halogen-free and flame-retardant properties, it still cannot overcome the defect that the density of the polyurethane foam material changes greatly due to the increase in the content of the flame retardant.
[0005] In summary, it can be seen that developing a polyurethane foam with low density and good flame retardant effect while ensuring that the foam has good performance is still a technical problem that urgently needs to be solved in this field. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a polyurethane foam and a preparation method thereof, which not only achieves a high flame retardant effect, but also maintains a low density of the rigid foam after foaming, and can fully meet the demand for foam for power batteries.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a polyurethane foam, wherein the raw materials for preparing the polyurethane foam include component A and component B;
[0009] The A component includes the following components in parts by weight:
[0010]
[0011] The B component includes the following components in parts by mass:
[0012] Isocyanate A 35-45 parts 8-10 parts of composite flame retardant.
[0013] In the present invention, the mass fraction of polyether polyol A is 15-25 parts, for example, it can be 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts or 24 parts.
[0014] The mass fraction of the polyester polyol is 10-15 parts, for example, it can be 10.5 parts, 11 parts, 11.5 parts, 12 parts, 12.5 parts, 13 parts, 13.5 parts, 14 parts or 14.5 parts.
[0015] The mass fraction of the composite flame retardant is 7-15 parts, for example, it can be 7.5 parts, 8 parts, 8.5 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts or 14 parts.
[0016] The mass fraction of the silane coupling agent A is 4-8 parts, for example, 4.5 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts or 7.5 parts.
[0017] The mass fraction of the hydrogen-containing silicone oil A is 0.5-1.5 parts, for example, it can be 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1.0 parts, 1.1 parts, 1.2 parts, 1.3 parts or 1.4 parts.
[0018] The mass fraction of the catalyst A is 0.01-0.15 parts, for example, it can be 0.01 parts, 0.02 parts, 0.03 parts, 0.04 parts, 0.05 parts, 0.08 parts, 0.1 parts, 0.12 parts or 0.14 parts.
[0019] The mass fraction of the ultrapure water is 0.1-0.5 parts, for example, it can be 0.15 parts, 0.2 parts, 0.25 parts, 0.3 parts, 0.35 parts, 0.4 parts or 0.45 parts.
[0020] The raw materials for preparing the polyurethane foam provided by the present invention include component A and component B, wherein component A includes specific contents of polyether polyol A, polyester polyol, composite flame retardant, silane coupling agent A, hydrogenated silicone oil A, catalyst A and ultrapure water, and component B includes specific contents of isocyanate A and composite flame retardant. By compounding the specific component A and component B, the obtained polyurethane foam is improved in terms of flame retardancy, dielectric strength and compression strength, and is also conducive to reducing its thermal conductivity and density, thereby meeting the requirements of foam for power batteries.
[0021] In the present invention, the polyurethane foam has good flame retardant effect by matching specific content of polyether polyol A, polyester polyol and isocyanate A. When the content of polyether polyol A is too high, the foam has poor flexibility; when the content of isocyanate is too high, it is easy to cause core burning problem.
[0022] In the present invention, hydrogen-containing silicone oil A is used to improve the uniformity and fineness of the pores, thereby affecting the strength and density.
[0023] Preferably, the polyether polyol A includes any one of polyether 220, polyether 330N, polyether 1000D and polyether 2000D, or a combination of at least two thereof.
[0024] Preferably, the polyester polyol includes any one of CM-580, SR-5586, PE-2811 and PE-2708, or a combination of at least two thereof.
[0025] Preferably, the silane coupling agent A includes any one of KH-570, Z-6040 and Z-6011 or a combination of at least two thereof.
[0026] Preferably, the hydrogen-containing silicone oil A includes any one of KF69, KF96 and KF99, or a combination of at least two of them.
[0027] Preferably, the catalyst A comprises any one of triethylenediamine, triethylenediamine, dibutyltin dilaurate and N,N-dimethylcyclohexylamine, or a combination of at least two thereof, and more preferably triethylenediamine and / or dibutyltin dilaurate.
[0028] Preferably, the mass fraction of the catalyst A is 0.03-0.1 parts.
[0029] In the present invention, catalyst A is preferably a combination of triethylenediamine and dibutyltin dilaurate, wherein the mass fraction of triethylenediamine is 0.01-0.05 parts, for example, it can be 0.015 parts, 0.02 parts, 0.025 parts, 0.03 parts, 0.035 parts, 0.04 parts or 0.045 parts, etc.; the mass fraction of dibutyltin dilaurate is 0.02-0.1 parts, for example, it can be 0.03 parts, 0.04 parts, 0.05 parts, 0.06 parts, 0.07 parts, 0.08 parts or 0.09 parts, etc.
[0030] Preferably, the isocyanate A includes any one of MDI 50, polymeric MDI 100 and polymeric MDI 200, or a combination of at least two thereof.
[0031] Preferably, the raw materials for preparing the composite flame retardant include polyether polyol B, isocyanate B, solid flame retardant, liquid flame retardant, hydrogen-containing silicone oil B, silane coupling agent B and catalyst B.
[0032] Preferably, the raw materials for preparing the composite flame retardant include, by weight:
[0033]
[0034]
[0035] In the present invention, the mass fraction of the polyether polyol B is 25-35 parts, for example, it can be 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts or 34 parts.
[0036] The mass fraction of the isocyanate B is 35-45 parts, for example, 36 parts, 37 parts, 38 parts, 39 parts, 40 parts, 41 parts, 42 parts, 43 parts or 44 parts.
[0037] The mass fraction of the solid flame retardant is 5-35 parts, for example, 8 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts, 28 parts, 30 parts or 33 parts.
[0038] The mass fraction of the liquid flame retardant is 10-15 parts, for example, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts or 15 parts.
[0039] The mass fraction of the hydrogen-containing silicone oil B is 0.5-1.5 parts, for example, it can be 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 1.1 parts, 1.2 parts, 1.3 parts or 1.4 parts.
[0040] The mass fraction of the silane coupling agent B is 4-8 parts, for example, it can be 4.2 parts, 4.5 parts, 4.8 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts or 7.5 parts.
[0041] The mass fraction of the catalyst B is 0.01-0.15 parts, for example, 0.02 parts, 0.03 parts, 0.04 parts, 0.05 parts, 0.08 parts, 0.1 parts, 0.12 parts or 0.14 parts.
[0042] In the present invention, the raw materials of the composite flame retardant include a specific content of polyether polyol, isocyanate B solid flame retardant, liquid flame retardant, hydrogenated silicone oil B, silane coupling agent B and catalyst B. Through the coordination between the components, the obtained composite flame retardant not only has a good flame retardant effect, but also has a lower density. The present invention optimizes the formula of the flame retardant to form a composite flame retardant with the properties of a foaming glue. When it is applied to polyurethane foam, because it has a lower density, its addition has little effect on the overall density of the polyurethane foam, avoiding the prior art, in order to improve the flame retardant effect of the polyurethane foam and increase the amount of the flame retardant, so that the density of the obtained polyurethane foam is greatly increased, affecting the weight of the battery module, and thus failing to meet the needs of the power battery foam.
[0043] Preferably, the polyether polyol B includes any one of polyether 220, polyether 330N, polyether 1000D and polyether 2000D, or a combination of at least two thereof.
[0044] Preferably, the isocyanate B includes any one of polyether 220, polyether 330N, polyether 1000D and polyether 2000D, or a combination of at least two thereof.
[0045] Preferably, the isocyanate B includes any one of polymeric MDI 50, polymeric MDI 100 and polymeric MDI 200, or a combination of at least two thereof.
[0046] Preferably, the solid flame retardant includes any one or a combination of at least two of aluminum hydroxide, magnesium hydroxide, boehmite, antimony trioxide, sodium silicate, potassium silicate, zinc borate and barium metaborate, and more preferably any one or a combination of at least two of aluminum hydroxide, magnesium hydroxide and boehmite.
[0047] Preferably, the mass fraction of the solid flame retardant is 5.5-17.5 parts, for example, it can be 5.5 parts, 6 parts, 8 parts, 10 parts, 12 parts, 14 parts, 16 parts, 16.5 parts, 17 parts or 17.5 parts.
[0048] In the present invention, the solid flame retardant is preferably a combination of aluminum hydroxide, magnesium hydroxide and boehmite, wherein the mass fraction of aluminum hydroxide is 2-7 parts, for example, it can be 2 parts, 2.5 parts, 3 parts, 4 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts or 7 parts; the mass fraction of magnesium hydroxide is 1.5-5.5 parts, for example, it can be 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts or 5.5 parts; the mass fraction of boehmite is 2-5 parts, for example, it can be 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts or 5 parts.
[0049] Preferably, the liquid flame retardant includes any one of triisopropylphenyl phosphate, dimethyl methyl phosphate, triphenyl phosphate and diethyl ethyl phosphate, or a combination of at least two thereof.
[0050] In the present invention, by adding a specific content of solid flame retardant and liquid flame retardant to the formation of a specific polyurethane, the prepared composite flame retardant has good flame retardant properties. When the content of the solid flame retardant increases, the solid flame retardant itself has a larger density, so that the density of the composite flame retardant increases accordingly. At the same time, due to excessive solid flame retardant, uneven dispersion, i.e., local agglomeration, is not conducive to the formation of the composite flame retardant; when the content of the liquid flame retardant increases, the dilution effect is enhanced, affecting the molding of the composite flame retardant. At the same time, the increase in the content of the phosphate liquid flame retardant will also affect the activity of the catalyst B, thereby affecting the formation reaction of the composite flame retardant.
[0051] Preferably, the hydrogen-containing silicone oil B includes any one of KF69, KF96 and KF99, or a combination of at least two of them.
[0052] Preferably, the silane coupling agent B includes any one of KH-570, Z-6040 and Z-6011 or a combination of at least two thereof.
[0053] Preferably, the catalyst B comprises any one of triethylenediamine, triethylenediamine, dibutyltin dilaurate and N,N-dimethylcyclohexylamine, or a combination of at least two thereof, and more preferably triethylenediamine and / or dibutyltin dilaurate.
[0054] Preferably, the mass fraction of the catalyst B is 0.03-0.1 parts.
[0055] In the present invention, catalyst B is preferably a combination of triethylenediamine and dibutyltin dilaurate, wherein the mass fraction of triethylenediamine is 0.01-0.05 parts, for example, it can be 0.015 parts, 0.02 parts, 0.025 parts, 0.03 parts, 0.035 parts, 0.04 parts or 0.045 parts, etc.; the mass fraction of dibutyltin dilaurate is 0.02-0.1 parts, for example, it can be 0.03 parts, 0.04 parts, 0.05 parts, 0.06 parts, 0.07 parts, 0.08 parts or 0.09 parts, etc.
[0056] Preferably, the preparation method of the composite flame retardant comprises:
[0057] The polyether polyol B, isocyanate B, solid flame retardant, liquid flame retardant, silane coupling agent B, hydrogen-containing silicone oil B and catalyst B are mixed and foamed, hardened, crushed and sieved.
[0058] Preferably, the curing time is 16-24 hours, for example, it can be 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours.
[0059] Preferably, the screening is through a 200-mesh sieve.
[0060] Preferably, the mass ratio of component A to component B is (0.9-1.1):1, for example, it can be 0.92:1, 0.95:1, 0.98:1, 1:1, 1.02:1, 1.05:1 or 1.08:1, etc.
[0061] In the present invention, component A and component B are mixed in a mass ratio of (0.9-1.1):1. When the mass ratio is higher than 1.1:1, the foam is not completely cured, the mechanical strength is low, and it is easy to cause shrinkage and collapse of the foam; when the mass ratio is lower than 0.9:1, the product is brittle and causes core burning in severe cases.
[0062] In a second aspect, the present invention provides a method for preparing the polyurethane foam as described in the first aspect, the preparation method comprising the following steps:
[0063] (1) Mix the components in component A and stir evenly;
[0064] (2) Mix the components in component B and stir evenly;
[0065] (3) The uniformly stirred component A and component B are mixed, poured, and foamed to obtain the polyurethane foam.
[0066] Preferably, the mixing temperature in step (1) is 15-45°C, for example, it can be 18°C, 20°C, 22°C, 25°C, 28°C, 30°C, 32°C, 35°C, 38°C, 40°C or 42°C.
[0067] Preferably, the stirring time in step (1) is ≥ 1 h.
[0068] Preferably, the mixing temperature in step (2) is 15-45°C, for example, 18°C, 20°C, 22°C, 25°C, 28°C, 30°C, 32°C, 35°C, 38°C, 40°C or 42°C.
[0069] Preferably, the stirring time in step (2) is ≥ 1 h.
[0070] Preferably, the mixing in step (3) is carried out under stirring.
[0071] Preferably, the stirring temperature is 15-45°C, for example, it can be 18°C, 20°C, 22°C, 25°C, 28°C, 30°C, 32°C, 35°C, 38°C, 40°C or 42°C.
[0072] Preferably, the stirring speed is 60-500 r / min, for example, 60 r / min, 100 r / min, 200 r / min, 300 r / min, 400 r / min or 500 r / min.
[0073] Preferably, the foaming time in step (3) is 6-10 min, for example, 6 min, 7 min, 8 min, 9 min or 10 min.
[0074] In the present invention, component A and component B are mixed and foamed directly, the mixing time is less than 5 minutes, and the foaming time is 6-10 minutes. Since the foaming starts slowly during the mixing process, the foaming time includes the mixing and stirring time. In addition, the surface dry time in the present invention is 15-30 minutes, for example, it can be 15 minutes, 18 minutes, 20 minutes, 22 minutes, 25 minutes, 28 minutes or 30 minutes.
[0075] In a third aspect, the present invention provides a use of the polyurethane foam as described in the first aspect in a power battery.
[0076] In power batteries, polyurethane foam is mainly used for battery protection, improving overall performance, filling gaps, replacing metal structural parts and waterproof sealing. These applications not only improve the safety and stability of power batteries, but also help improve the performance and range of electric vehicles.
[0077] Compared with the prior art, the present invention has at least the following beneficial effects:
[0078] (1) The present invention adds a specific composite flame retardant to make the obtained polyurethane foam have excellent flame retardant properties and low density; at the same time, the present invention compounded a specific component A with a component B to improve the flame retardant properties, dielectric strength and compressive strength of the obtained polyurethane foam, while also helping to reduce its thermal conductivity and density, thereby meeting the needs of foam for power batteries;
[0079] (2) The density of the polyurethane foam of the present invention after foaming is not higher than 0.25 g / mL, the flame retardant grade is UL94-V0, the dielectric strength is greater than 3 kV / mm, the thermal conductivity is less than 0.1 W / (m·K), and the compressive strength is greater than 3 MPa. DETAILED DESCRIPTION
[0080] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0081] Preparation Example 1
[0082] A composite flame retardant, the preparation method of which comprises: mixing 30 parts of polyether 220, 40 parts of PM100, 4 parts of aluminum hydroxide, 3 parts of boehmite, 1.91 parts of magnesium hydroxide, 15 parts of triisopropylphenyl phosphate, 5 parts of KH-570, 1 part of KF96, 0.03 parts of triethylenediamine and 0.06 parts of dibutyltin dilaurate at 25°C for 10 minutes, standing for foaming and forming, hardening for 24 hours, measuring the density of the composite flame retardant to be 0.30, and crushing and passing through a 200-mesh sieve to obtain the composite flame retardant.
[0083] Preparation Example 2
[0084] A composite flame retardant, the preparation method of which comprises: mixing 25 parts of polyether 220, 45 parts of PM100, 3 parts of aluminum hydroxide, 4 parts of boehmite, 1.91 parts of magnesium hydroxide, 15 parts of triisopropylphenyl phosphate, 5 parts of KH570, 1 part of KF96, 0.03 parts of triethylenediamine and 0.06 parts of dibutyltin dilaurate at 25°C for 10 minutes, standing for foaming and hardening for 24 hours, measuring a density of 0.28, and crushing and passing through a 200-mesh sieve to obtain the composite flame retardant.
[0085] Preparation Example 3
[0086] A composite flame retardant, the preparation method of which comprises: mixing 35 parts of polyether 220, 35 parts of PM100, 4 parts of aluminum hydroxide, 3 parts of boehmite, 1.91 parts of magnesium hydroxide, 15 parts of triisopropylphenyl phosphate, 5 parts of KH570, 1 part of KF96, 0.03 parts of triethylenediamine and 0.06 parts of dibutyltin dilaurate at 25°C for 10 minutes, standing for foaming and forming, hardening for 24 hours, measuring the density of the composite flame retardant to be 0.35, and crushing and passing through a 200-mesh sieve to obtain the composite flame retardant.
[0087] Preparation Example 4
[0088] The only difference between this preparation example and preparation example 1 is that the mass fractions of the following components are adjusted as follows: 8 parts of aluminum hydroxide, 5 parts of boehmite, 5.91 parts of magnesium hydroxide, and 5 parts of triisopropylphenyl phosphate. The other components, amounts, and preparation methods are the same as those in preparation example 1.
[0089] Preparation Example 5
[0090] The only difference between this preparation example and preparation example 1 is that the mass fractions of the following components are adjusted as follows: 1 part of aluminum hydroxide, 2 parts of boehmite, 0.91 parts of magnesium hydroxide, and 20 parts of triisopropylphenyl phosphate. The other components, amounts, and preparation methods are the same as those in preparation example 1.
[0091] Example 1
[0092] This embodiment provides a polyurethane foam, wherein the raw materials for preparing the polyurethane foam include component A and component B;
[0093] The A component includes the following components in parts by weight:
[0094]
[0095] The B component includes the following components in parts by weight:
[0096] PM100 40 copies 10 parts of composite flame retardant.
[0097] Among them, the mass ratio of component A to component B is 1:1.
[0098] The preparation method of the polyurethane foam comprises the following steps:
[0099] (1) According to the formula, polyether 220, CM-580, composite flame retardant (Preparation Example 1), Z-6040, KF69, triethylenediamine, dibutyltin dilaurate and ultrapure water were mixed at 25° C. and stirred for 2 h to obtain component A;
[0100] (2) PM100 and the composite flame retardant (Preparation Example 1) were mixed at 25° C. according to the formula and stirred for 1.5 h to obtain component B;
[0101] (3) Component A and component B in a mass ratio of 1:1 were stirred and mixed at a speed of 200 r / min for 4 min, poured into a mold, and allowed to stand for foaming and forming. The total foaming time was 10 min and the surface was dried for 20 min to obtain the polyurethane foam.
[0102] Example 2
[0103] This embodiment provides a polyurethane foam, wherein the raw materials for preparing the polyurethane foam include component A and component B;
[0104] The A component includes the following components in parts by weight:
[0105]
[0106] The B component includes the following components in parts by weight:
[0107] PM100 45 copies 10 parts of composite flame retardant.
[0108] Among them, the mass ratio of component A to component B is 1.1:1.
[0109] The preparation method of the polyurethane foam comprises the following steps:
[0110] (1) According to the formula, polyether 220, CM-580, composite flame retardant (Preparation Example 1), Z-6040, KF69, triethylenediamine, dibutyltin dilaurate and ultrapure water were mixed at 45° C. and stirred for 1 hour to obtain component A;
[0111] (2) PM100 and the composite flame retardant (Preparation Example 1) were mixed at 45° C. according to the formula and stirred for 1 h to obtain component B;
[0112] (3) Component A and component B with a mass ratio of 1.1:1 were stirred and mixed at a speed of 60 r / min for 2 min, poured into a mold, and allowed to stand for foaming and forming. The total foaming time was 8 min, and the surface was dried for 30 min to obtain the polyurethane foam.
[0113] Example 3
[0114] This embodiment provides a polyurethane foam, wherein the raw materials for preparing the polyurethane foam include component A and component B;
[0115] The A component includes the following components in parts by weight:
[0116]
[0117] The B component includes the following components in parts by weight:
[0118] PM100 35 copies 8 parts of composite flame retardant.
[0119] Among them, the mass ratio of component A to component B is 0.9:1.
[0120] The preparation method of the polyurethane foam comprises the following steps:
[0121] (1) According to the formula, polyether 220, CM-580, composite flame retardant (Preparation Example 1), Z-6040, KF69, triethylenediamine, dibutyltin dilaurate and ultrapure water were mixed at 15° C. and stirred for 4 hours to obtain component A;
[0122] (2) PM100 and the composite flame retardant (Preparation Example 1) were mixed at 15° C. according to the formula and stirred for 3 h to obtain component B;
[0123] (3) Component A and component B with a mass ratio of 0.9:1 were stirred and mixed at a speed of 500 r / min for 3 minutes, poured into a mold, and allowed to stand for foaming and forming. The total foaming time was 6 minutes and the surface was dried for 15 minutes to obtain the polyurethane foam.
[0124] Example 4
[0125] This embodiment provides a polyurethane foam, which differs from Example 1 in that the composite flame retardant obtained in Preparation Example 2 is used to replace the composite flame retardant obtained in Preparation Example 1, and other components, amounts and preparation methods are the same as those in Example 1.
[0126] Example 5
[0127] This embodiment provides a polyurethane foam, which differs from Example 1 in that the composite flame retardant obtained in Preparation Example 3 is used to replace the composite flame retardant obtained in Preparation Example 1, and other components, amounts and preparation methods are the same as those in Example 1.
[0128] Example 6
[0129] This embodiment provides a polyurethane foam, which differs from Embodiment 1 in that the composite flame retardant obtained in Preparation Example 4 is used to replace the composite flame retardant obtained in Preparation Example 1, and other components, amounts and preparation methods are the same as those in Embodiment 1.
[0130] Example 7
[0131] This embodiment provides a polyurethane foam, which differs from Embodiment 1 in that the composite flame retardant obtained in Preparation Example 5 is used to replace the composite flame retardant obtained in Preparation Example 1, and other components, amounts and preparation methods are the same as those in Embodiment 1.
[0132] Example 8
[0133] This embodiment provides a polyurethane foam, which is different from Example 1 in that the mass ratio of component A to component B is 0.8:1, and other components, amounts and preparation methods are the same as those in Example 1.
[0134] Example 9
[0135] This embodiment provides a polyurethane foam, which is different from Embodiment 1 in that the mass ratio of component A to component B is 1.2:1, and other components, amounts and preparation methods are the same as those in Embodiment 1.
[0136] Comparative Example 1
[0137] This comparative example provides a polyurethane foam, which is different from Example 1 in that no composite flame retardant is added to component A and component B, and other components, amounts and preparation methods are the same as those in Example 1.
[0138] Comparative Example 2
[0139] This comparative example provides a polyurethane foam, which is different from Example 1 in that component A does not contain a composite flame retardant, and other components, amounts and preparation methods are the same as those in Example 1.
[0140] Comparative Example 3
[0141] This comparative example provides a polyurethane foam, which is different from Example 1 in that no composite flame retardant is added to component B, and other components, amounts and preparation methods are the same as those in Example 1.
[0142] Comparative Example 4
[0143] This comparative example provides a polyurethane foam, which differs from Example 1 in that a mixed flame retardant (obtained by blending 4 parts of aluminum hydroxide, 3 parts of boehmite, 1.91 parts of magnesium hydroxide and 15 parts of triisopropylphenyl phosphate) is used to replace the composite flame retardant obtained in Preparation Example 1, and other components, amounts and preparation methods are the same as those in Example 1.
[0144] Comparative Example 5
[0145] This comparative example provides a polyurethane foam, which differs from Example 1 in that the mass fraction of the composite flame retardant in component A is adjusted to 6 parts, and the other components, amounts and preparation methods are the same as those in Example 1.
[0146] Comparative Example 6
[0147] This comparative example provides a polyurethane foam, which differs from Example 1 in that the mass fraction of the composite flame retardant in component A is adjusted to 16 parts, and the other components, amounts and preparation methods are the same as those in Example 1.
[0148] Comparative Example 7
[0149] This comparative example provides a polyurethane foam, which differs from Example 1 in that the mass fraction of the composite flame retardant in component B is adjusted to 7 parts, and the other components, amounts and preparation methods are the same as those in Example 1.
[0150] Comparative Example 8
[0151] This comparative example provides a polyurethane foam, which differs from Example 1 in that the mass fraction of the composite flame retardant in component B is adjusted to 11 parts, and other components, amounts and preparation methods are the same as those in Example 1.
[0152] Comparative Example 9
[0153] This comparative example provides a polyurethane foam, which differs from Example 1 in that the polyether 220 in component A is adjusted to 26 parts, and the CM-580 is adjusted to 6 parts, and the other components, amounts and preparation methods are the same as those in Example 1.
[0154] Comparative Example 10
[0155] This comparative example provides a polyurethane foam, which differs from Example 1 in that PM100 in component B is adjusted to 30 parts, and other components, amounts and preparation methods are the same as those in Example 1.
[0156] Comparative Example 11
[0157] This comparative example provides a polyurethane foam, which differs from Example 1 in that PM100 in component B is adjusted to 46 parts, and other components, amounts and preparation methods are the same as those in Example 1.
[0158] Comparative Example 12
[0159] This comparative example provides a polyurethane foam, which is different from Example 1 in that KF69 is not added to component A, and other components, amounts and preparation methods are the same as those in Example 1.
[0160] Comparative Example 13
[0161] This comparative example provides a polyurethane foam, which is different from Example 1 in that CM-580 is not added to component A, and other components, amounts and preparation methods are the same as those in Example 1.
[0162] At 25° C., the polyurethane foams provided in Examples 1-9 and Comparative Examples 1-13 were tested using the following test methods:
[0163] (1) Flame retardant performance test: horizontal and vertical combustion test machine;
[0164] (2) Density test: drainage method;
[0165] (3) Dielectric strength: AC / DC withstand voltage insulation analyzer;
[0166] (4) Thermal conductivity test: thermal conductivity tester;
[0167] (5) Compression strength test: universal testing machine.
[0168] The test results are shown in Table 1:
[0169] Table 1
[0170]
[0171]
[0172] The test results show that:
[0173] (1) It can be seen from Examples 1-9 that the polyurethane foam obtained by compounding specific components A and B has excellent flame retardant properties and a low density; the density of the polyurethane foam obtained by the present invention after foaming is not higher than 0.25 g / mL, the flame retardant grade is UL94-V0, the dielectric strength is greater than 3 kV / mm, the thermal conductivity is less than 0.1 W / (m·K), and the compressive strength is greater than 3 MPa.
[0174] (2) By comparing Example 1 with Comparative Examples 1-3, it can be seen that the addition of the specific composite flame retardant in component A and component B can effectively improve the flame retardant properties of the obtained polyurethane foam.
[0175] (3) By comparing Example 1 with Comparative Example 4, it can be seen that the addition of the specific composite flame retardant in the present invention can significantly reduce the density of the obtained polyurethane foam and help improve its flame retardant properties.
[0176] (4) By comparing Example 1 with Comparative Examples 5-8, it can be seen that if the content of the composite flame retardant in component A or component B is too low, the flame retardancy of the obtained polyurethane foam material will be poor, and if the content of the composite flame retardant is too high, the thermal conductivity of the polyurethane foam will increase, which is not conducive to the flame retardant effect.
[0177] (5) By comparing Example 1 with Comparative Examples 9-11, it can be seen that the addition of specific contents of polyether polyol A, polyester polyol and isocyanate A can improve the flame retardant properties, dielectric strength and compressive strength of the obtained polyurethane foam, while helping to reduce its density and thermal conductivity.
[0178] (6) By comparing Example 1 with Comparative Example 12, it can be seen that the addition of specific hydrogen-containing silicone oil can improve the dielectric strength and compressive strength of the polyurethane foam while also helping to reduce its thermal conductivity and density.
[0179] In summary, the present invention, by adding a specific composite flame retardant, makes the obtained polyurethane foam have excellent flame retardant properties and a lower density; at the same time, by compounding a specific A component with a B component, the present invention makes the obtained polyurethane foam have improved flame retardant properties, dielectric strength and compressive strength, etc., and is also conducive to reducing its thermal conductivity and density, thereby meeting the needs of foam for power batteries.
[0180] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A polyurethane foam, characterized in that: The raw materials for preparing the polyurethane foam include component A and component B; The A component includes the following components in parts by weight: The B component includes the following components in parts by weight: Isocyanate A 35-45 parts, composite flame retardant 8-10 parts.
2. The polyurethane foam according to claim 1, characterized in that: The polyether polyol A includes any one of polyether 220, polyether 330N, polyether 1000D and polyether 2000D, or a combination of at least two thereof; Preferably, the polyester polyol includes any one or a combination of at least two of CM-580, SR-5586, PE-2811 and PE-2708; Preferably, the silane coupling agent A includes any one or a combination of at least two of KH-570, Z-6040 and Z-6011; Preferably, the hydrogen-containing silicone oil A comprises any one or a combination of at least two of KF69, KF96 and KF99; Preferably, the catalyst A comprises any one of triethylenediamine, triethylenediamine, dibutyltin dilaurate and N,N-dimethylcyclohexylamine or a combination of at least two thereof, and more preferably triethylenediamine and / or dibutyltin dilaurate; Preferably, the mass fraction of the catalyst A is 0.03-0.1 parts; Preferably, the isocyanate A includes any one of polymeric MDI 50, polymeric MDI 100 and polymeric MDI 200, or a combination of at least two thereof.
3. The polyurethane foam according to claim 1 or 2, characterized in that: The raw materials for preparing the composite flame retardant include polyether polyol B, isocyanate B, solid flame retardant, liquid flame retardant, hydrogen-containing silicone oil B, silane coupling agent B and catalyst B.
4. The polyurethane foam according to claim 3, characterized in that: The raw materials for preparing the composite flame retardant include, by weight:
5. The polyurethane foam according to claim 3 or 4, characterized in that: The polyether polyol B includes any one of polyether 220, polyether 330N, polyether 1000D and polyether 2000D, or a combination of at least two thereof; Preferably, the isocyanate B comprises any one or a combination of at least two of polymeric MDI 50, polymeric MDI 100 and polymeric MDI 200; Preferably, the solid flame retardant includes any one or a combination of at least two of aluminum hydroxide, magnesium hydroxide, boehmite, antimony trioxide, sodium silicate, potassium silicate, zinc borate and barium metaborate, and more preferably any one or a combination of at least two of aluminum hydroxide, magnesium hydroxide and boehmite; Preferably, the mass fraction of the solid flame retardant is 5.5-17.5 parts; Preferably, the liquid flame retardant comprises any one or a combination of at least two of triisopropylphenyl phosphate, dimethyl methyl phosphate, triphenyl phosphate and diethyl ethyl phosphate; Preferably, the hydrogen-containing silicone oil B includes any one or a combination of at least two of KF69, KF96 and KF99; Preferably, the silane coupling agent B includes any one or a combination of at least two of KH-570, Z-6040 and Z-6011; Preferably, the catalyst B comprises any one of triethylenediamine, triethylenediamine, dibutyltin dilaurate and N,N-dimethylcyclohexylamine or a combination of at least two thereof, and more preferably triethylenediamine and / or dibutyltin dilaurate; Preferably, the mass fraction of the catalyst B is 0.03-0.1 parts.
6. The polyurethane foam according to any one of claims 3 to 5, characterized in that: The preparation method of the composite flame retardant comprises: The polyether polyol B, isocyanate B, solid flame retardant, liquid flame retardant, silane coupling agent B, hydrogen-containing silicone oil B and catalyst B are mixed and foamed, hardened, crushed and sieved.
7. The polyurethane foam according to claim 6, characterized in that: The hardening time is 16-24h; Preferably, the screening is through a 200-mesh sieve.
8. The polyurethane foam according to claims 1-7, characterized in that: The mass ratio of component A to component B is (0.9-1.1):
1.
9. A method for preparing the polyurethane foam according to claims 1-8, characterized in that: The preparation method comprises the following steps: (1) Mix the components in component A and stir evenly; (2) Mix the components in component B and stir evenly; (3) mixing the above-mentioned components A and B which have been stirred evenly, pouring, and foaming to obtain the polyurethane foam; Preferably, the mixing temperature in step (1) is 15-45°C; Preferably, the stirring time in step (1) is ≥ 1 h; Preferably, the mixing temperature in step (2) is 15-45°C; Preferably, the stirring time in step (2) is ≥ 1 h; Preferably, the mixing in step (3) is carried out under stirring; Preferably, the stirring temperature is 15-45°C; Preferably, the stirring speed is 60-500r / min; Preferably, the foaming time in step (3) is 6-10 min.
10. Use of the polyurethane foam according to any one of claims 1 to 8 in a power battery.
Citation Information
Patent Citations
Polyurethane foam material for cylindrical battery module as well as preparation method and application of polyurethane foam material
CN115368527A
Cited By
High-hardness and low-density flame-retardant polystyrene foam for unmanned aerial vehicle and preparation method thereof
CN119410327A
A high-hardness, low-density flame-retardant foam for drones and a preparation method thereof
CN119410327B
